2018
DOI: 10.1097/mao.0000000000001980
|View full text |Cite
|
Sign up to set email alerts
|

Hearing Restoration During Vestibular Schwannoma Surgery With Transcanal Approach: Anatomical and Functional Preliminary Report

Abstract: Transcanal retrocochlear approach for VS removal allows preservation of cochlea and cochlear nerve function. This is the first step towards developing an effective surgical technique for VS removal and hearing rehabilitation with CI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…11 For small acoustic neuromas confined to the internal auditory meatus, the scala tympani is retained when opening and exposing the cochlea middle turn and top turn. 12 Using our surgical approach, we also found that we did not need to open and expose the cochlea middle turn and top turn, and we avoided damage to the residual hearing of the cochlea by extending the vestibular window and grinding part of the promontorium tympani. We removed the acoustic neuromas directly through the internal auditory meatus.…”
Section: Discussionmentioning
confidence: 87%
“…11 For small acoustic neuromas confined to the internal auditory meatus, the scala tympani is retained when opening and exposing the cochlea middle turn and top turn. 12 Using our surgical approach, we also found that we did not need to open and expose the cochlea middle turn and top turn, and we avoided damage to the residual hearing of the cochlea by extending the vestibular window and grinding part of the promontorium tympani. We removed the acoustic neuromas directly through the internal auditory meatus.…”
Section: Discussionmentioning
confidence: 87%
“…4,19 While commonly used for resection of cholesteatoma and tympanoplasty, the endoscope has also been successfully utilized to resect ILS and ensure macroscopic clearance of disease. 4,8,12,20 Pan and colleagues 4 reported an endoscopic-assisted resection of an ILS in 2019. This was followed by Ma et al, 8 who in 2020 reported an endoscopic-assisted resection of ICS followed by immediate cochlear implantation.…”
Section: Discussionmentioning
confidence: 99%
“…18,23,47 Optimizing CI rehabilitation has potential to help the NF2 population. 25,[48][49][50][51][52][53][54][55] Still, caution should be advised when patients have a large tumor burden. Future data on patient quality of life and long-term outcomes are needed before this approach can be more broadly accepted.…”
Section: Discussionmentioning
confidence: 99%